Prospective Evaluation of Antibody Response post COVID-19 vaccination in older persons ≧ 60 years old (PEARL 60): A longitudinal 15-months study in a tertiary centre in Malaysia - Kejal Hasmukharay; Ashutosh Kumar Verma; Kiirtaara Aravindhan; Prakhaash Raaj S. Alagappan; Aisya Karynna Md Kamal; Nurul Syuhada Zulhaimi; Nor Izzati Saedon; Jamal I-Ching-Sam; Tan Maw Pin; Reena Rajasuriar (PLoS ONE, 2026)
Older adults exhibit heterogeneous immune responses to COVID-19 vaccination, yet the relative contributions of age, comorbidity, vaccine platform, and infection history to antibody durability remain incompletely defined. Understanding these determinants is essential to inform booster strategies in ageing populations. We conducted a longitudinal observational study of 300 participants (250 aged ≥60 years and 50 younger controls) followed for up to 15 months. Anti-spike (anti-S) antibody responses were assessed at four event-anchored timepoints: ≤ 3 months post-primary vaccination (TP1), ~ 3 months post-first booster (TP2), 6–9 months post-first booster capturing waning immunity (TP3), and ≤3 months post-second booster where available (TP4). Multivariable log-linear regression models were used to identify independent determinants of antibody levels, with additional analyses stratified by infection status and vaccine platform. Among older adults, 78.8% had moderate-to-severe comorbidity burden, 40.0% were pre-frail, and only 16.8% received a second booster. At TP3, older age was associated with lower antibody levels in univariable analysis (GMR 0.81, 95% CI 0.68–0.97) but not after adjustment (aGMR 0.78, 95% CI 0.51–1.22, p = 0.279). Independent predictors of higher TP3 antibody levels included female sex (aGMR 1.24, 95% CI 1.02–1.51, p = 0.028), prior SARS-CoV-2 infection (aGMR 1.39, 95% CI 1.14–1.71, p = 0.001), and mRNA (aGMR 5.16, 95% CI 3.57–7.47, p=<0.001) or viral vector boosters (aGMR 6.05, 95% CI 4.03–9.08, p=<0.001), while renal disease was associated with lower responses (aGMR 0.71, 95% CI 0.54–0.94, p = 0.017). Similar associations were observed at TP4. Frailty and sarcopenia were not independently associated with antibody levels. Neutralising antibodies against Omicron were absent after primary vaccination and detected in only 25.9% of infection-naïve older adults after the first booster. Sustained humoral immunity following COVID-19 vaccination is driven primarily by vaccine platform and immune history rather than chronological age or geriatric syndromes alone. Waning immunity unmasks vulnerability in older adults, while low uptake of second boosters highlights a critical gap between immunological risk and vaccine utilisation. These findings support targeted, equity-focused booster strategies prioritising highly immunogenic platforms and high-risk older adults.